The influence of salary, working environment, and workload on academician's job satisfaction - Hazirah Izzati, Samsul Kahar (2025)
This paper aims in analysing the influence of salary, working environment and workload towards academician’s job satisfaction. The research attempt to examine the relationship between salary, working environment and workload with academician’s job satisfaction. The study employs quantitative approach to investigate the hypothesis and identify the impact of salary, working environment and workload towards academician’s job satisfaction. The study has been conducted among academicians and received 63 valid respondents in a private college located in Kuantan, Pahang, Malaysia. Data were gathered by questionnaire survey and analysed by using SPSS. Findings reveal that there is a positive significant relationship on both salary and working environment towards academician’s job satisfaction and it was discovered that workload is not significant in affecting academician’s job satisfaction. The findings indicate that salary and working environment are seen as key factors, although workload does not appear to have a statistically significant effect on academic staff job satisfaction